Aplicação de sistemas de equações lineares ao funcionamento do GPS - Sampaio, Carlos Eduardo Francisco (2023)
In this work, essential mathematical concepts present in the functioning of the Global Positioning System (GPS), popularly known as GPS, will be presented. We will emphasize linear equation systems, which have been chosen as the object of study for this research, with the aim of stimulating students’ interest in mathematics by demonstrating how theoretical concepts learned in the classroom have practical applications in our daily lives. We will present the theory of matrices and linear systems, using their matrix representation and solution techniques, such as Gaussian elimination and Cramer’s rule, to provide the necessary mathematical foundation for understanding the subject. Additionally, we will explore the history and operation of GPS, from its creation during the Cold War period, with the NAVSTAR project led by the United States Department of Defense, to its omnipresence in our lives today, permeating our lives in various ways.